Transcriptomic analysis of wound-healing in Solanum tuberosum (potato) tubers: Evidence for a stepwise induction of suberin-associated genes. (February 2023) - Woolfson, Kathlyn N.; Zhurov, Vladimir; Wu, Tian; Kaberi, Karina M.; Wu, Stephanie; Bernards, Mark A.
Abstract: Suberin deposition involves both phenolic and aliphatic polymer biosynthesis and deposition in the same tissue. Therefore, any consideration of exploiting suberin for crop enhancement (e.g., enhanced storage, soil borne disease resistance) requires knowledge of both phenolic and aliphatic component biosynthesis and their coordinated, temporal deposition. In the present study, we use a wound-healing potato tuber system to explore global transcriptome changes during the early stages of wound-healing. Wounding leads to initial and substantial transcriptional changes that follow distinctive temporal patterns – primary metabolic pathways were already functional, or up-regulated immediately, and maintained at levels that would allow for precursor carbon skeletons and energy to feed into downstream metabolic processes. Genes involved in pathways for phenolic production (i.e., the shikimate pathway and phenylpropanoid metabolism) were up-regulated early while those involved in aliphatic suberin production (i.e., fatty acid biosynthesis and modification) were transcribed later into the time course. The pattern of accumulation of genes associated with ABA biosynthesis and degradation steps support a role for ABA in regulating aliphatic suberin production. Evaluation of putative Casparian strip membrane-like genes pinpointed wound-responsive candidates that may mediate the suberin deposition process. Graphical abstract: Wounding of potato tubers results in a large-scale change in transcription with temporal differences in expression of phenolic and aliphatic suberin biosynthesis genes. Image 1 Highlights: Wounding induces an initial large-scale change in gene expression. Fine-tuning of gene expression occurs over several days. Phenolic and aliphatic suberin biosynthesis genes are differentially upregulated.